ANALISIS PENGARUH KARAKTERISTIK PEMDA, INDEKS PEMBANGUNAN MANUSIA, DAN KUALITAS HASIL AUDIT TERHADAP TINGKAT PENGUNGKAPAN LKPD - Usrotun Najah (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2019)
The purpose of this study is aimed to determine the influence of the characteristics of region governments. The characteristics includes the regional government’s wealth; balance funds; and the level of regional financial independence, the Human Development Index, and the BPK's audit quality results which includes findings; deviation level; and audit opinion toward the level of disclosure in local government financial statements. The populations in this study are all the Local Government Financial Reports of regencies and cities in Central and East Java. The number of samples in this study were 130 Local Government Financial Statements. The result of this study shows that: Regional Government Wealth and Regional Financial Independence Ratios significantly influences the Local Government Financial Statement disclosure level, while Intergovernmental Revenue; The Human Development Index; Audit Findings; Audit Deviation Levels; and Audit Opinions did not significantly influences the Local Government Financial Statement disclosure level.